2019
DOI: 10.21055/0370-1069-2019-2-55-61
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of Yersinia pestis Strains of Medieval Biovar, Isolated in Precaspian North-Western Steppe Plague Focus in the XX Century

Abstract: Objective of the study – comparative phylogenetic analysis of Yersinia pestis strains, isolated in Precaspian North-Western steppe focus in 1924–1926, 1972, and 1986–1990 to understand the causes of focal reactivation during different time periods of the XX century.Materials and methods. The work included 30 strains of Yersinia pestis from Precaspian North-Western steppe natural focus and adjacent plague foci. Whole genome sequencing of eight Y. pestis strains from the former was carried out. Also whole-genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…At the end of the 19th century and beginning of the 20th, numerous outbreaks of plague were registered in the Northern Caspian Sea region in Russia and Kazakhstan. Our studies prove that since 1912, outbreaks in the Northern Caspian Sea region have been caused by Y. pestis strains of the phylogenetic branches 2.MED1 and 2.MED4 of the medieval biovar ( 3 , 4 ). The study of the genomes of the etiological agents of plague outbreaks in the Northern Caspian Sea region at the beginning of the 20th century is important for elucidating the causes of the high mortality rates among the population, as well as for historical reconstruction of the evolution of the medieval biovar of the plague pathogen.…”
Section: Announcementsupporting
confidence: 62%
“…At the end of the 19th century and beginning of the 20th, numerous outbreaks of plague were registered in the Northern Caspian Sea region in Russia and Kazakhstan. Our studies prove that since 1912, outbreaks in the Northern Caspian Sea region have been caused by Y. pestis strains of the phylogenetic branches 2.MED1 and 2.MED4 of the medieval biovar ( 3 , 4 ). The study of the genomes of the etiological agents of plague outbreaks in the Northern Caspian Sea region at the beginning of the 20th century is important for elucidating the causes of the high mortality rates among the population, as well as for historical reconstruction of the evolution of the medieval biovar of the plague pathogen.…”
Section: Announcementsupporting
confidence: 62%
“…During the period from the beginning of the 20th century till present days, while performing epidemiological and epizootiological monitoring in the natural foci of plague in the Caspian Sea and Aral Sea regions, specialists of the Plague Control System of the Soviet Union, and then Russia have gathered a unique collection of Y. pestis strains, which chronologically reflects the history of the foci. According to microbiological and molecular genetic studies of a large number of strains, it was revealed that in the foci of the Caspian and Aral Sea regions Y. pestis of the medieval biovar circulates [1,3]. The strains of this biovar are highly virulent and epidemiologically significant.…”
Section: Introductionmentioning
confidence: 99%